A genetic pathway composed of Sox14 and Mical governs severing of dendrites during pruning. - Kirilly, D.; Gu, Y.; Huang, Y.; Wu, Z.; Bashirullah, A.; Low, B.C.; Kolodkin, A.L.; Wang, H.; Yu, F. (Nature Neuroscience, 2009)
Pruning that selectively eliminates neuronal processes is crucial for the refinement of neural circuits during development. In Drosophila, the class IV dendritic arborization neuron (ddaC) undergoes pruning to remove its larval dendrites during metamorphosis. We identified Sox14 as a transcription factor that was necessary and sufficient to mediate dendrite severing during pruning in response to ecdysone signaling. We found that Sox14 mediated dendrite pruning by directly regulating the expression of the target gene mical. mical Encodes a large cytosolic protein with multiple domains that are known to associate with cytoskeletal components. mical Mutants had marked severing defects during dendrite pruning that were similar to those of sox14 mutants. Overexpression of Mical could significantly rescue pruning defects in sox14 mutants, suggesting that Mical is a major downstream target of Sox14 during pruning. Thus, our findings indicate that a previously unknown pathway composed of Sox14 and its cytoskeletal target Mical governs dendrite severing.